«Воспитательно-образовательные возможности авторской песни на примере песни В.Моисеевой "О Войне" и песни "Гурзуф" из цикла песен В. Моисеевой «Крымские Арабески»» - Moiseeva V. V. (Educational environment today: theory and practice, 2021)
Today there is an acute problem of educating the creative potential of the younger generations, their artistic taste, preferences. Among the goals and objectives of education - the formation of artistic thinking (and as a variety - musical thinking) is very relevant. Therefore, the article considers some problems of the development of creative activity as the basis of artistic and musical thinking. Based on the study of the methodology of working on songs, it is necessary to determine the effectiveness of the influence of the author's song for voice and piano accompaniment on the formation of holistic ideas about the surrounding nature, the social environment of the cities of Crimea, the place of a person in it, self-esteem, the harmonious manifestation of patriotic feelings. Creation and testing of a song cycle as an accompanying material in solving the tasks of the regional component in education.
Keywords: преподаватель; учитель; аккомпанемент; мелодия; музыкант; композитор; поэт; автор; Крым; цикл; teacher; crimea; author; melody; poet; composer; accompaniment; sevastopol; арабески; Симферополь; Гурзуф; Ялта; Джанкой; musician; cycle; arabesques; gurzuf; about the war; simferopol; simeiz; kerch; feodosia; dzhankoy; krasnoperekopsk